Performance of the highly sensitive humidity sensor constructed with nanofibrillated cellulose/graphene oxide/polydimethylsiloxane aerogel via freeze drying. Issue 3 (5th January 2021) - Yang, Yutong; Su, Guoting; Li, Qilin; Zhu, Zipiao; Liu, Shaoran; Zhuo, Bing; Li, Xinpu; Ti, Pu; Yuan, Quanping
Abstract : This work presents a nanocellulose-based humidity sensor with high sensitivity, remarkable reproducibility and rapid response/recovery behavior fabricated via freeze drying. Abstract : A kind of capacitive humidity sensor with high sensitivity constructed with nanofibrillated cellulose (NFC), graphene oxide (GO) and polydimethylsiloxane (PDMS) is presented in this work, via a simple ultrasonic dispersion and freeze drying technology. The NFC and GO with a strong adsorption for water molecules were used as a substrate for the promotion of capacitive response of the humidity sensor. Moreover, anhydrous ethanol was added to inhibit the generation of big cracks in the humidity sensor in the freeze drying process, so as to obtain a regular network porous structure, then providing a great deal of conduction channels and active sites for molecular water. Also, the addition of PDMS can effectively enhance the flexibility and stability of its porous structure. The results confirmed that the humidity sensor with 30 wt% GO showed an excellent humidity sensitivity (6576.41 pF/% RH), remarkable reproducibility, low humidity hysteresis characteristic in 11–97% relative humidity (RH) at 25 °C, and short response/recovery times (57 s/2 s). In addition, the presented sensor exhibited small relative deviation of the measured relative humidity value compared with the commercial hygrometer. The realization of the high sensitivity can be attributed to the theories about interaction of the hydrophilic group, proton transfer of water molecules and the three-dimensional network transport structure model. Therefore, the NFC/GO/PDMS humidity sensor finally realizes stable, reproducible and fast humidity sensing via an eco-friendly process, exhibiting promising potential for wide practical application.